Face to Face Consumption According to Conventional and Islamic Concept - Basrowi Basrowi; Ruslan Abdul Ghofur (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Pekalongan, 2019)
The purpose of this study is to get detailed answers to the differences between consumption concepts from conventional and Islamic perspectives. Face to face comparison is believed to provide a complete picture of the differences in these two perspectives. The method used to answer the above problems is by qualitative methods, precisely the method of literature. The results of the in-depth study show that there are very essential differences between the concepts of consumption according to conventional and Islamic perspectives. The difference is not only in values, principles, but also in the application of daily application. This research gives a new perpective in the scientific repertoire of consumption concepts according to Islam because it is able to present differences face to face to get clarity on a phenomenon